Find α+β+αβ

Tags:
1. Apr 11, 2017

donaldparida

1. The problem statement, all variables and given/known data
P(x) =ax2+bx+c where a, b and c are in arithmetic progression and are positive. α and β are the roots of the equation and are integers. Find the value of α+β+αβ. (Answer is 7)
2. Relevant equations
x = {−b ± √(b2 − 4ac)} /2a
3. The attempt at a solution

Since a, b and c are in arithmetic progression, b-a=c-b.
α+β+αβ = -b/a+c/a = c-b/a = b-a/a

2. Apr 11, 2017

scottdave

You know that α and β are roots, so k*(x - α)(x - β) is equal to the polynomial. Expand this out with FOIL k*(x² - (α+β)x + αβ), set this equal to ax² + bx + c. Since they are roots, you do not know what the coefficient of x squared is, yet. So you can represent that k*(x² - (α+β)x + αβ) = ax² + bx + c. Now set the coefficients of the x² terms equal, the x terms, and the constant terms. This should give you a system of equations (along with your knowledge of the arithmetic progression). See if that gets you the answer.

3. Apr 11, 2017

donaldparida

@scottdave, What is k?

Last edited: Apr 11, 2017
4. Apr 11, 2017

scottdave

k is a constant which makes the two polynomials equal. You can have several distinct polynomials with the same roots. The difference is a proportionality constant. You will find that k is equal to a.

5. Apr 11, 2017

donaldparida

@scottdave Do you mean that equations which are related by a multiplicative factor have equal roots?

6. Apr 11, 2017

donaldparida

Sorry, but i am not getting the answer. I am getting some weird equation.

7. Apr 11, 2017

Staff: Mentor

Add brackets around the numerator and simplify.

You can also use the condition that the roots are integers.

8. Apr 11, 2017

donaldparida

@mfb, i cannot understand how to simplify it further.

9. Apr 11, 2017

Staff: Mentor

$$\frac{b-a}{a} = \frac b a - \frac a a$$
And the second term can be simplified.

Afterwards you can have a look at the condition that α and β are integers.

10. Apr 11, 2017

donaldparida

@mfb, I thought you meant some other simplification. I could do that simplification by myself but i cannot simplify it further. I am getting -(α+β )-1=α+β+αβ. I cannot recall any related property of integer which would help me simplify it further.

11. Apr 11, 2017

Staff: Mentor

α+β+αβ = b/a - 1. Keep that result for now.

α and β are integers. What does that imply for α+β+αβ?
What does it imply if you look at the formula for α (or β)?

12. Apr 11, 2017

donaldparida

I found out that if α or β are integers, then [{−b ± √(b2 − 4ac)} /2a] must also be integers. ('s' in 'integers' is due to the ± sign).

For them to be integers {−b ± √(b2 − 4ac)} and 2a must also be integers and {−b ± √(b2 − 4ac)} must be a multiple of 2a.

For {−b ± √(b2 − 4ac)} to be integer and an multiple of 2a, -b and √(b2 − 4ac) should be integers and should leave the same remainder on dividing by 2a.
For -b to be an integer b should be an integer (positive, given in the question) and for √(b2 − 4ac) to be an integer (b2 − 4ac) has to be a positive integer as well as a perfect square.

The most important conclusion is (b2 − 4ac) is a perfect square.

13. Apr 11, 2017

Staff: Mentor

That directly follows from the definition, yes.
Why? You can show that, but it is not trivial.
Sure.
Right so far.

14. Apr 11, 2017

donaldparida

(i)If α and β are integers then α+β+αβ is also an integer.
(ii) b2>=4ac
=>(b/a)(b/c)>=4
=>-(α+β)(b/c)>=4
=>-(α+β){(b*a)/(c*a)}>=4
=>-(α+β)*[{-(α+β)}/αβ]>=4
=>(α+β)2/αβ>=4
=>(α+β)2/>=4αβ
=>α22+2αβ-4αβ>=0
=>(α-β)2>=0
=>α>=β

15. Apr 11, 2017

Staff: Mentor

A squared real number is always >=0, there is no need to derive this over 9 lines.
That does not follow from the previous line.
Correct. And you know that α+β+αβ = b/a - 1. That tells you if b/a has to be an integer.

If b/a is an integer, you can rewrite your arithmetic progression and express c in terms of a and b. That should lead to some interesting results in the square root - which needs a perfect square in it.

16. Apr 12, 2017

donaldparida

Did you mean this
b-a=c-b
=>b-a+b=c
=>2b-a=c
=>2ak-a=c
=>a(2k-1)=c
or this
b-a=ak-b
=>2b-a-ak=0
=>2b-a(1+k)=0

17. Apr 12, 2017

Staff: Mentor

If a, b, and c are the coefficients of a quadratic equation, what is the sum of the roots and what is the product of the roots?

18. Apr 12, 2017

donaldparida

19. Apr 12, 2017

Staff: Mentor

I'm not sure you used this, so $$\alpha + \beta +\alpha\beta=\frac{c-b}{a}$$Certainly, this isn't generally equal to 7, even for an arithmatic progression.

20. Apr 12, 2017

Staff: Mentor

We also know $\alpha$ and $\beta$ are integers.
The problem is solvable, but it needs a few steps to get there.
Both will work, but the first definition of k is much more intuitive.

Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted